O tratamento do crédito fiscal na recuperação judicial - Masson, Bruno Uzilin (2025)
Throughout the evolution of both the interpretation and practical application of the Brazilian Bankruptcy and Judicial Reorganization Law, a prevailing understanding has emerged regarding the mandatory proof of tax compliance as a condition for the granting of judicial reorganization. This requirement fosters not only debate concerning the normative regulation and the functionality of the legal instruments available to the debtor for addressing tax liabilities, but also the consequences arising from noncompliance with legal provisions. This study adopts the hypothetical-deductive method, supported by bibliographical and jurisprudential research as it’s methodological approach. The conclusions reached are as follows: 1. Although two negotiation instruments are provided for under the applicable law – tax settlement (transação) and installment plan (parcelamento) – their regulation remains sparse and insufficient within the State of São Paulo, hindering the debtor’s access to tax compliance; 2. The practical implementation of procedural legal transactions, despite their functional and expedited nature – which aims to ensure judicial efficiency and economy – is rarely applied, and even less frequently regulated; 3. Failure to prove tax compliance cannot justify the declaration of bankruptcy, both due to the absence of legal provision and the counterproductive effects such a measure would have on the purposes of the reorganization process; 4. The legal consequence of breaching an agreement with the tax authorities – namely, the conversion of reorganization into bankruptcy – is not always the most favorable outcome, whether for the debtor, the creditors, or the broader economic context in which the company operates, especially considering the social function of the enterprise and the objectives of judicial reorganization; and 5. It is appropriate to consider, as a potential improvement to the process of resolving public credit claims, the ongoing communication among the parties, with active participation by the court and the judicial administrator, not merely as passive recipients of information submitted by the debtor, but as direct contributors to the success of the tax liability restructuring.